The prevalence of orthorexia nervosa in patients with selected chronic diseases - Ciulkiewicz, Łukasz; Figurowska, Patrycja; Małek, Natalia; Kwiatkowska, Anita; Pluta, Patryk; Karłowicz, Konrad; Brożyna, Aleksandra; Emerla, Sara; Hermanowska, Maria; Lubomirska, Julia; et al. (Journal of Education, Health and Sport, 2024)
Introduction and aim. Orthorexia nervosa is described as an obsession with consuming solely healthy foods accompanied by restrictive behaviors. Patients with chronic conditions frequently require dietary interventions alongside medication to manage symptoms and slow down disease progression. However, when dietary restrictions are taken to extremes, individuals may develop orthorexia nervosa, resulting in malnutrition and weight loss. This poses risks during treatment, where maintaining a balanced diet is vital. In this review we aim to display the prevalence of orthorexia nervosa in patients suffering from selected chronic diseases. Material and methods. A literature review was performed to investigate the prevalence of orthorexia nervosa in individuals with type 1 diabetes, inflammatory bowel disease, celiac disease, rheumatoid arthritis, and cancer. Description of the State of Knowledge. The occurrence of orthorexia reaches up to 7% in the general population, 72% in patients with type 1 diabetes mellitus, 77% in case of inflammatory bowel disease, 71% among individuals suffering from celiac disease, 75% in those with rheumatoid arthritis, and 50% in case of cancer. Orthorexia nervosa mostly affects females who are younger, have higher education levels, select organic foods, prepare their own meals, and have concurrent chronic illnesses. Distress associated with diagnosis is the primary factor contributing to the development of this condition. Orthorexia ultimately leads to malnutrition, weight loss, impaired social functioning, and poses a risk of complications in chronically ill patients. Conclusion. The prevalence of orthorexia nervosa in patients suffering from chronic illnesses is significantly higher compared to the general population. Therefore, early detection of this condition and intervention are necessary to improve patient management. Further research is needed to assess the frequency of orthorexia among individuals suffering from other chronic diseases.